How to Improve Speaking Skill using Treffinger Learning Model? - Rizqi Akbarani (Makassar State University, 2019)
This research analyzed the implementation of Treffinger learning model in teaching speaking skill. This research used n classroom action research by applying treffinger learning model in speaking class. In collecting the data, research used observation to observe the implementation of Treffinger learning model during teaching learning process and used speaking test to find the improvement of students’ speaking skill during implementation of Treffinger learning model. The research finding showed that the implementation of Treffinger learning model can improve the students’ speaking skill. Thereore, it can be concluded that Treffinger learning model is acceptable to be used as teaching learning model in teaching speaking.